The Word ‘LOOK’ in Corpus of Contemporary American English (COCA) - Anne Merialfianti; Ervina C M Simatupang (Jurnal Sinestesia, 2023)
This research aims to analyze and describe the word classes of the word look and their meaning. The method used in this research qualitative method. The data used were taken from Corpus of Contemporary American English (COCA). This is a research about morphology, syntax and semantics studies. The theoretical basis used in identifying word classes are Burkette (2018), O’Grady (1997) and Downing (1994) theory to identifying the meaning types. The result of this study show that there are four word classes, they are verb, noun, exclamation and phrasal verb. The results showed that out of 30 data that have been analyzed, the word classes were obtained namely 3 verb data (10 %), 5 noun data (16,6 %), 2 exclamation data (6,6 %) and 20 phrasal verb data (66,7 %). It can be concluded that the word look as a phrasal verb is the most word classes that occur with 66,7 %. The most word classes that occur is phrasal verb. Semantically there are three types of meaning, they are literal meaning, semi-idiomatic meaning and idiomatic meaning. Meanwhile, the types of meaning are literal meaning, semi- idiomatic meaning and idiomatic meaning. The types of meanings found are 11 data of literal meaning (36,6%), 7 data of semi- idiomatic meaning (23,3 %) and 12 data of idiomatic meaning (40 %). It can also be concluded that the most meaning types of word look is idiomatic meaning with 40 %.